ANALISIS FRAMING PEMBERITAAN PERMENDIKBUD TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI DI MEDIA ONLINE - Avian Savitri, Lulu; Manalu, S. Rouli; Hasfi, Nurul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Permendikbud No. 30 of 2021 reflects the government's commitment to preventing and handling sexual violence in universities. However, its implementation triggered debates in various aspects such as religion, socio-culture, and law. Detik.com and Kumparan.com are examples of online media that provide a forum for public discussion on controversial issues related to the regulation. By applying constructivist framing analysis, this study reveals three frames used by online media Detik.com and Kumparan.com, namely